Cardiovascular Effects of Autologous Bone Marrow-Derived Mesenchymal Stromal Cell Therapy With Early Tacrolimus Withdrawal in Renal Transplant Recipients: An Analysis of the Randomized TRITON Study - Meucci Maria Chiara; Reinders Marlies E. J.; Groeneweg Koen E.; Bezstarosti Suzanne; Marsan Nina Ajmone; Bax Jeroen J.; De Fijter Johan W.; Delgado Victoria (Wiley, 2022)
Background
After renal transplantation, there is a need of immunosuppressive regimens that effectively prevent allograft rejection while minimizing cardiovascular complications. This substudy of the TRITON trial evaluated the cardiovascular effects of autologous bone marrow–derived mesenchymal stromal cells (MSCs) in renal transplant recipients.
Methods and Results
Renal transplant recipients were randomized to MSC therapy, infused at weeks 6 and 7 after transplantation, with withdrawal at week 8 of tacrolimus or standard tacrolimus dose. Fifty‐four patients (MSC group=27; control group=27) underwent transthoracic echocardiography at weeks 4 and 24 after transplantation and were included in this substudy. Changes in clinical and echocardiographic variables were compared. The MSC group showed a benefit in blood pressure control, assessed by a significant interaction between changes in diastolic blood pressure and the treatment group (P=0.005), and a higher proportion of patients achieving the predefined blood pressure target of <140/90 mm Hg compared with the control group (59.3% versus 29.6%, P=0.03). A significant reduction in left ventricular mass index was observed in the MSC group, whereas there were no changes in the control group (P=0.002). The proportion of patients with left ventricular hypertrophy decreased at 24 weeks in the MSC group (33.3% versus 70.4%, P=0.006), whereas no changes were noted in the control group (63.0% versus 48.1%, P=0.29). Additionally, MSC therapy prevented progressive left ventricular diastolic dysfunction, as demonstrated by changes in mitral deceleration time and tricuspid regurgitant jet velocity.
Conclusions
MSC strategy is associated with improved blood pressure control, regression of left ventricular hypertrophy, and prevention of progressive diastolic dysfunction at 24 weeks after transplantation.